Park scientists : Gila monsters, geysers, and grizzly bears in America's own backyard - Carson, Mary Kay (Scientists in the field., 2014)
Describes the work of scientists in America's national parks, as they study geysers, grizzly bears, salamanders, cacti, and fireflies.